The Implementation of Merdeka Belajar Kampus Merdeka Through Adaptive Learning Program and Curriculum Development - Pattipawaej, Olga; Setiawan, Deni; Desiani, Asriwiyanti; Tallar, Robby; ., Abdul Rahmat (KnE Social Sciences, 2023)
Merdeka Belajar Kampus Merdeka (MBKM), a program of the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia, enables students to learn about practical knowledge and gain important skills for their future employment. The program was implemented by the Civil Engineering Department at Universitas Kristen Maranatha through projects on curriculum development and adaptive learning programs. Four tasks were carried out namely, project-based learning modules, curriculum preparation, curriculum drafting, and curriculum finalization. The goals were to meet the key performance indicators (KPI) of higher education. Keywords: adaptive learning, curriculum development, key performance indicators, Merdeka Belajar Kampus Merdeka